Prochlorperazine Induced Dystonia / Dyskinesia : Mimicking As Acute Stroke (Journal of Pharmaceutical Negative Results, 2022)
Prochlorperazine is frequently used in the treatment of refractory nausea and migraines. Known side effects include extrapyramidal symptoms such as akathisia, dyskinesia and dystonia. We report a hypertensive male taking prochlorperazine for dizziness and vomiting in ward who developed hemidystonia, which triggered an acute Code Stroke Response .